2005
DOI: 10.1103/physreva.71.063810
|View full text |Cite
|
Sign up to set email alerts
|

Stimulated Rayleigh-Bragg scattering in two-photon absorbing media

Abstract: The origin and mechanism of backward stimulated Rayleigh scattering in two-photon absorbing media are studied theoretically and experimentally. This type of stimulated scattering has the unusual features of no frequency shift and low pump threshold requirement compared to all other known stimulated scattering effects. This frequency-unshifted stimulated Rayleigh scattering effect can be well explained by a two-photonexcitation-enhanced Bragg grating reflection model. The reflection of the forward pump beam fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 25 publications
2
26
1
Order By: Relevance
“…17 shows good agreement with the results of this model. To get an order of magnitude of the numbers involved, consider the experiment of He et al 16,17 and the results shown in Figure 6. For a laser wavelength of 532 nm and T e ~ 1 ns, 5,26 I sat ~ 0.7 GW/cm 2 .…”
Section: Stimulated Scatteringsupporting
confidence: 87%
See 4 more Smart Citations
“…17 shows good agreement with the results of this model. To get an order of magnitude of the numbers involved, consider the experiment of He et al 16,17 and the results shown in Figure 6. For a laser wavelength of 532 nm and T e ~ 1 ns, 5,26 I sat ~ 0.7 GW/cm 2 .…”
Section: Stimulated Scatteringsupporting
confidence: 87%
“…20,21 It is possible however, under TPA resonant conditions, that n 2 could have a finite response time (i.e., χ (3) is complex with a finite damping coefficient 21 ). However, if this is included in the development of the coupled-wave intensity equations, it would lead to a term in the gain G that is proportional to I L , not 2 L I , which would be inconsistent with the experimental results of He et al 17 It is also quite likely that the Kerr refractive term would be much smaller than the term proportional to…”
Section: Stimulated Scatteringmentioning
confidence: 78%
See 3 more Smart Citations